2022
DOI: 10.1037/stl0000238
|View full text |Cite
|
Sign up to set email alerts
|

Applying positive psychology to foster student engagement and classroom community amid the COVID-19 pandemic and beyond.

Abstract: Positive psychology is the study of well-being, which includes 5 essential elementspositive emotions, engagement, relationships, meaning, and accomplishment (PERMA). Applying positive psychology teaching strategies can therefore foster student engagement and classroom community, especially in an online modality and during the novel coronavirus disease 2019 (COVID-19) pandemic in which social connections are more important and yet harder to establish than ever. The aims of this teacher-ready theory review are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
0
20
0
2
Order By: Relevance
“…For an e-servicescape to become a new (virtual) service marketplace, at the micro level, e-learners’ collaborative learning and instructors’ online teaching strategies should be promoted and trained to reinforce individualised ways of online interacting (Paulsen and McCormick, 2020). These can result in better study outcomes and well-being by strengthening student engagement in online lectures (Chu, 2020), and individual psychological benefits by enhancing campus attachment (Scannell and Gifford, 2017). At the meso level, educational service providers should pay more attention to integrating the e-servicescape for online teaching and learning with the physical campus servicescape to improve the student experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For an e-servicescape to become a new (virtual) service marketplace, at the micro level, e-learners’ collaborative learning and instructors’ online teaching strategies should be promoted and trained to reinforce individualised ways of online interacting (Paulsen and McCormick, 2020). These can result in better study outcomes and well-being by strengthening student engagement in online lectures (Chu, 2020), and individual psychological benefits by enhancing campus attachment (Scannell and Gifford, 2017). At the meso level, educational service providers should pay more attention to integrating the e-servicescape for online teaching and learning with the physical campus servicescape to improve the student experience.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the dramatic change in the education sector, student engagement in online lectures has also attracted extensive attention, as it has significant impact on a university’s service ecosystem consisting of students, instructors, administrative and other staff as well as available resources (Carter and Yeo, 2016; Finsterwalder and Kuppelwieser, 2020). Enhanced student engagement can contribute to highly valued educational outcomes, such as students’ improved academic achievement, enhanced teaching practice for instructors and better managed and developed services for educational institutions (Chu, 2020; Ogunmokun et al , 2021).…”
Section: Conceptual Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing psychological and emotional support to K-12 online-learning students is crucial for student learning and wellbeing (Chu, 2020;COL, 2020). Simpson (2013) illustrates that caring human support at a distance facilitates self-directed learning, reduces student isolation and creates an environment for student engagement in learning.…”
Section: Learner Supportsmentioning
confidence: 99%
“…After discarding duplicate works, a total of three studies were identified. The analysis of each of them resulted in: (a) a qualitative research about the trauma approach in conjunction with applied positive psychology for elementary school teachers (Brunzell et al, 2021 ); (b) a study focused on coping strategies in relation to well-being, stress and negative emotions in language teachers at different teaching levels (MacIntyre et al, 2020 ); and (c) a theoretical proposal focused on methods and teaching strategies based on well-being and positive psychology for teachers but focused on student well-being (Chu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%